Pemanfaatan Media Ssosial oleh Tenaga Kerja Indonesia dalam Proses Pendidikan Anak Menggunakan Metode Belajar Long Distance Relationship - Basrowi Basrowi (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2019)
At present, social media is more widely used by migrant workers and TKI children just for the daily communication. The function of the social media is done in trivialities because both parties operationally can maximazie the media more specifically especially to improve the process of education and learning between parents to their children. This study draws problem of how social media can be used by TKI in educating children, through the LDR (Long Distance Relationship) method. This study used qualitative descriptive approach to analyze the data. The research subjects who acted as respondents were migrant workers and former migrant workers from Lampung Province. The results show that learning models using the LDR Method could be applied by Indonesian migrant workers to children who live in their hometowns. Themes of communication using LDR should be focused on education aspects emphasizing on motivation, achievement, frame of future life, and daily activities for schools.